2016
DOI: 10.1145/2935746
|View full text |Cite
|
Sign up to set email alerts
|

GPU-Accelerated Generation of Correctly Rounded Elementary Functions

Abstract: Abstract-The IEEE 754-2008 standard recommends the correct rounding of some elementary functions. This requires to solve the Table Maker's Dilemma which implies a huge amount of CPU computation time. We consider in this paper accelerating such computations, namely Lefèvre algorithm on Graphics Processing Units (GPUs) which are massively parallel architectures with a partial SIMD execution (Single Instruction Multiple Data).We first propose an analysis of the Lefèvre hard-to-round argument search using the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…These two steps are massively parallel over the domains D i since these numerous domains can all be processed independently. However, while the polynomial approximation generation has a regular control flow [9], the HR-case search presents divergence issues when executed on SIMD architectures. Moreover, the HR-case search is the most time consuming step when solving the TMD.…”
Section: Midpointsmentioning
confidence: 99%
See 4 more Smart Citations
“…These two steps are massively parallel over the domains D i since these numerous domains can all be processed independently. However, while the polynomial approximation generation has a regular control flow [9], the HR-case search presents divergence issues when executed on SIMD architectures. Moreover, the HR-case search is the most time consuming step when solving the TMD.…”
Section: Midpointsmentioning
confidence: 99%
“…In [22], Lefèvre tested other variants of this strategy and concluded that in practice the most efficient strategy was this three phases refinement. This is mainly due to the fact that the number of arguments succeeding the existence test can be roughly predicted, and that the amount of time spent in the HR-case existence test has to be balanced with the amount of time spent in exhaustive search [9,22]. Algorithm 1: Lefèvre three phases isolation strategy for HR-case search.…”
Section: Midpointsmentioning
confidence: 99%
See 3 more Smart Citations